On Certain Inequalities for Neuman-Sándor Mean. (26th May 2013) - Qian, Wei-Mao; Chu, Yu-Ming
Abstract : We present several new sharp bounds for Neuman-Sándor mean in terms of arithmetic, centroidal, quadratic, harmonic root square, and contraharmonic means.